Spatial pattern and correlates of maternal healthcare utilization in the North Eastern Region of India: evidence from the National Family Health Survey, 2019–2021 - Gajendra Gupta; Tejbir Singh Rana; Sadanand Karun; Ankita Roy (Discover Public Health)
Abstract Utilization of maternal healthcare services such as four or more antenatal care visits (4+ ANC), delivery by a skilled birth attendant (Del-SBA), and postnatal care (PNC) is crucial for better pregnancy outcomes and reducing maternal and child mortality. Northeast India faces serious maternal health issues as Assam records the highest maternal mortality ratio in the country. Therefore, the present study aims to examine the spatial patterns and determinants of maternal healthcare utilization in Northeast India. The choropleth mapping, bivariate analysis, and logistic regression were applied to the National Family Health Survey-5 data to assess the spatial pattern and determinants of maternal healthcare services utilization. We found that the levels of 4+ ANC, Del-SBA, and PNC were 49.7%, 79.1%, and 69.7%, respectively, in Northeast India, which is lesser than the national level. The state and district-level patterns indicate significant disparities in the utilization of 4+ ANC, PNC, and Del-SBA. Among north-eastern states, Manipur had the highest level of 4+ ANC, and Sikkim had the highest level of PNC and Del-SBA. On the other hand, Nagaland performs worst in utilizing all three maternal health services. Women with exposure to mass media, higher educational level, Hindu religion, rich wealth quintile and urban residence were significantly more likely to utilize maternal healthcare services than their counterparts. Additionally, beneficiaries of government programmes such as the Janani Suraksha Yojana, health insurance, and mother and child protection cards were significantly more likely to utilize maternal healthcare services. In conclusion, to increase maternal healthcare utilization in northeastern states, special attention is required for women belonging to poor wealth status, scheduled castes and scheduled tribes, living in rural areas, and having no education. In addition, raising awareness and tailored policy intervention is needed in Nagaland and districts closer to international borders.